2010
DOI: 10.1152/japplphysiol.00883.2009
|View full text |Cite
|
Sign up to set email alerts
|

Operational point of neural cardiovascular regulation in humans up to 6 months in space

Abstract: Entering weightlessness affects central circulation in humans by enhancing venous return and cardiac output. We tested whether the operational point of neural cardiovascular regulation in space sets accordingly to adopt a level close to that found in the ground-based horizontal position. Heart rate (HR), finger blood and brachial blood pressure (BP), and respiratory frequency were collected in 11 astronauts from nine space missions. Recordings were made in supine and standing positions at least 10 days before … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
48
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(57 citation statements)
references
References 50 publications
7
48
2
Order By: Relevance
“…The reduction in baroreflex sensitivity after spaceflight is consistent with our findings during bed rest and those of other bed rest studies (13,15,28,39,57). Spaceflight has also been shown to cause changes in autonomic function similar to those we found in bed rest, such as diminished vagal activity (2,16,22,62), increased sympathetic activity (11,22,26,30,31), and increased sympathovagal balance (2,30). Future studies should specifically address whether the sex differences in autonomic function and baroreflex sensitivity observed in our bed rest study are also present during and after spaceflight.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The reduction in baroreflex sensitivity after spaceflight is consistent with our findings during bed rest and those of other bed rest studies (13,15,28,39,57). Spaceflight has also been shown to cause changes in autonomic function similar to those we found in bed rest, such as diminished vagal activity (2,16,22,62), increased sympathetic activity (11,22,26,30,31), and increased sympathovagal balance (2,30). Future studies should specifically address whether the sex differences in autonomic function and baroreflex sensitivity observed in our bed rest study are also present during and after spaceflight.…”
Section: Discussionsupporting
confidence: 91%
“…Multiple studies have examined autonomic function or baroreflex sensitivity during and after spaceflight; however, these studies consisted of entirely or mostly male subject groups, precluding the possibility of examining sex differences (2, 11, 16, 19, 22, 25, 29 -31, 62). Although some studies have found that baroreflex sensitivity in flight is decreased (22) or similar to that in the supine position preflight (19,62), most studies have agreed that baroreflex sensitivity is decreased after spaceflight (16,29,30). The reduction in baroreflex sensitivity after spaceflight is consistent with our findings during bed rest and those of other bed rest studies (13,15,28,39,57).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…There is also increasing evidence that many clinical effects of microgravity and most changes affecting the cardiovascular system after return from space are induced by alterations of the autonomic neural control (Mano 2005), which includes the baroreflex. While unchanged in-flight baroreflex was reported during long-term missions on the ISS Verheyden et al 2010), reduction of baroreflex response has been observed after both short-term (FritschYelle et al 1994;Gisolf et al 2005;Verheyden et al 2007) and long-term spaceflight and it has been suggested that the post-flight reductions in baroreflex response could be attributed to reductions in resting parasympathetic activity Verheyden et al 2010).…”
Section: Cardiovascular Effectsmentioning
confidence: 99%
“…Reduced circulating blood volume, reduced arterial diastolic blood pressure, reduced left ventricular mass, and decreases in ventricular stroke volume have been reported in numerous studies on the physiological effects of microgravity during spacefl ight ( 2,29 ). Some studies using hermetically sealed environments (110 d and 240 d) ( 12 ) and prolonged bed rest (120-180 d) ( 17 ) observed decreases in hormonal patterns of blood volume regulation during long-term confi nement, which might result from the elimination of mobility and action.…”
mentioning
confidence: 99%